(untitled) (Observatorio Económico, 2011)
The Ingreso Ético Familiar (Ethical Family Income) program seeks to benefit some 620,000 people—roughly 170,000 households—living in extreme poverty. In this sense, the program is seen as a continuation of the Chile Solidario program, whose target population as of 2001 was Chile’s 225,000 poorest families. There have, however, been many disagreements surrounding this initiative. Early in the year, over the launch of the Social Allowance Program (Programa de Asignación Social), regarded as a lukewarm start to this major campaign promise. Later, over the rejection of its budget appropriations for 2012. Continue reading...